2011
DOI: 10.1152/japplphysiol.01345.2010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic continuous positive airway pressure (CPAP) reduces airway reactivity in vivo in an allergen-induced rabbit model of asthma

Abstract: Previous studies have demonstrated that chronic mechanical strain produced by continuous positive airway pressure (CPAP) reduces in vivo airway reactivity in rabbits and ferrets. For CPAP to potentially have a therapeutic benefit for asthmatic subjects, the reduction in airway responsiveness would need to persist for 12-24 h after its discontinuation, require application for only part of the day, and be effective in the presence of atopic airway inflammation. In the present study, airway responsiveness to acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…Using in vivo animal models, our laboratory has demonstrated that chronic mechanical strain of the lung produced by continuous positive airway pressure (CPAP) can result in lower airway reactivity in vivo and in vitro [9, 10]. We recently reported that the administration of high CPAP (6 cmH 2 O) to rabbits for 4 days followed by 1 day of low CPAP (0 cmH 2 O) resulted in a persistent reduction of in vivo airway responsiveness compared with rabbits treated with low CPAP for 5 days [11]. In addition, the positive effects of high CPAP in rabbits could also be obtained by using only nocturnal high CPAP for the same time period [11].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Using in vivo animal models, our laboratory has demonstrated that chronic mechanical strain of the lung produced by continuous positive airway pressure (CPAP) can result in lower airway reactivity in vivo and in vitro [9, 10]. We recently reported that the administration of high CPAP (6 cmH 2 O) to rabbits for 4 days followed by 1 day of low CPAP (0 cmH 2 O) resulted in a persistent reduction of in vivo airway responsiveness compared with rabbits treated with low CPAP for 5 days [11]. In addition, the positive effects of high CPAP in rabbits could also be obtained by using only nocturnal high CPAP for the same time period [11].…”
mentioning
confidence: 99%
“…We recently reported that the administration of high CPAP (6 cmH 2 O) to rabbits for 4 days followed by 1 day of low CPAP (0 cmH 2 O) resulted in a persistent reduction of in vivo airway responsiveness compared with rabbits treated with low CPAP for 5 days [11]. In addition, the positive effects of high CPAP in rabbits could also be obtained by using only nocturnal high CPAP for the same time period [11]. Lastly, chronic high CPAP also suppressed in vivo airway reactivity in the presence of allergic airway inflammation, rabbits sensitised and challenged with ovalbumin [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One potential mechanism is a functional change in airway smooth muscles via airway stretching during increased ventilation with endurance-type exercise interventions in asthmatics. Although results regarding the effect of repetitive passive airway stretching by use of continuous positive airway pressure (CPAP) on bronchial hyperresponsiveness in asthmatic humans at rest are conflicting [4, 5], research in animals has shown that repetitive passive airway stretching via CPAP [6] or the removal thereof via chest wall strapping [7] have the potential to alter airway smooth muscle contractility and to decrease (or increase) bronchial hyperresponsiveness. Thus, isolated respiratory exercises such as volitional hyperpnea (HYP) without concomitant exercise could be an alternative to whole-body exercise training or an even more effective airway-specific treatment to complement regular exercise training since higher levels of ventilation and larger tidal volumes can be achieved compared to those present during strenuous physical exercise of the same duration [8].…”
Section: Introductionmentioning
confidence: 99%
“…CPAP also decreased airway reactivity in a rabbit model of asthma with atopic airway inflammation and airway hyperreactivity (18). Preliminary data derived from 16 individuals with asthma showed that 1 week of nocturnal 10 cm H 2 O CPAP was associated with a greater than twofold increase in the concentration of methacholine required to cause a 20% fall in FEV 1 (PC 20 ), as compared with 9 individuals with asthma who received sham CPAP (19).…”
mentioning
confidence: 95%